A View of the CP/DP-(non)parallelism from the Cartographic Perspective - Christopher Laenzlinger (Languages, 2017)
The aim of this paper is to reconsider some aspects of the so-called clause/noun-phrase (non-)parallelism (Abney 1987 and much subsequent work). The question that arises is to find out what is common and what is different between the clause as a Complementizer Phrase (CP)-structure and the noun as a Determiner Phrase (DP)-structure in terms of structure and derivation. An example of structural parallelism lies in the division of the clause and the noun phrase into three domains: (i) the Nachfeld (right periphery), which is the thematic domain; (ii) the Mittelfeld (midfield), which is the inflection, agreement, Case and modification domain and (iii) the Vorfeld (left periphery), which is the discourse- and operator-related domain. However, we will show following Giusti (2002, 2006), Payne (1993), Bruening (2009), Cinque (2011), Laenzlinger (2011, 2015) among others that the inner structure of the Vorfeld and of the Mittelfeld of the clause is not strictly parallel to that of the noun phrase. Although derivational parallelism also lies in the possible types of movement occurring in the CP and DP domains (short head/X-movement, simple XP-movement, remnant XP-movement and pied-piping XP-movement), we will see that there is non-parallelism in the application of these sorts of movement within the clause and the noun phrase. In addition, we will test the respective orders among adverbs/adjectives, DP/Prepositional Phrase (PP)-arguments and DP/PP-adjuncts in the Mittelfeld of the clause/noun phrase and show that Cinque’s (2013) left–right asymmetry holds crosslinguistically for the possible neutral order (without focus effects) in post-verbal/nominal positions with respect to the prenominal/preverbal base order and its impossible reverse order.